2009
DOI: 10.2146/ajhp080236
|View full text |Cite
|
Sign up to set email alerts
|

Stability of gabapentin 300-mg capsules repackaged in unit dose containers

Abstract: Gabapentin 300-mg capsules in the original containers and repackaged in blister strips were stable up to one year under long-term storage conditions and up to three months under accelerated storage conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 12 publications
2
4
0
9
Order By: Relevance
“…Thus, a study was carried out to investigate the stability of ranitidine syrup repackaged in unit dose containers, and the results revealed that the syrup is stable for up to 52 weeks when stored at room temperature conditions. 12 Similar findings were also reported by Gupta et al, 13 who examined the stability of gabapentin capsules that were repackaged in unit dose containers and found that the repackaged capsules were stable for up to one year under long-term storage conditions (i.e., 25 ºC and 60% relative humidity).…”
supporting
confidence: 71%
“…Thus, a study was carried out to investigate the stability of ranitidine syrup repackaged in unit dose containers, and the results revealed that the syrup is stable for up to 52 weeks when stored at room temperature conditions. 12 Similar findings were also reported by Gupta et al, 13 who examined the stability of gabapentin capsules that were repackaged in unit dose containers and found that the repackaged capsules were stable for up to one year under long-term storage conditions (i.e., 25 ºC and 60% relative humidity).…”
supporting
confidence: 71%
“…Badaniom stabilności poddawane są także przepakowane leki w postaci syropów. Autorzy publikacji wykazują, że przepakowanie leków w systemie unit dose nie wpływa na ich stabilność [1,11,60,61,62]. Amerykańska Agencja ds.…”
Section: Funkcjonowanie Automatycznych Systemów Dystrybucji Leków W Punclassified
“…Analizowano także piśmiennictwo pod kątem stabilności przepakowywanych leków w dawkach jednostkowych. [20,21,22,23,24,25]. Wśród artykułów dotyczących występowania błędów medycznych podczas korzystania z systemu unit dose trzy opisywały błędy w trakcie przepisywania leków [9,17,18], dwa podczas ich przygotowywania [19,16], a pięć w trakcie administracji leków [9,14,15,16,18] (tab.…”
Section: El P Ra C Yunclassified
“…Wśród włączonych badań trzy dotyczą stabilności leków po przepakowaniu w dawki jednostkowe [24,25,26]. Poruszane są w nich kwestie rozkładu leku [24], zanieczyszczeń [26], zmiany koloru [24,26], wagi [25,26], pH [26] i mocy [25] (tab. VI).…”
Section: Mat E Ri Ał I M Eto D Yunclassified